Regional Development Policies of Commonwealth Countries in Africa - Bedjour, George Amponsah (Univerzita Pardubice, 2023)
The roots of the regional policies came about in Great Britain at the beginning of the 20th century. Many countries in the world left the Empire of Great Britain during the last century, but they are keeping close economic and social relations with the United Kingdom through the Commonwealth. The provision of aid and other forms of help to less economically developed regions is where regional development's significance lies. The diffusion of regional policy ideas into the governance of these African countries may have been aided by this. Using Ghana, Zambia, Rwanda, and South Africa as case studies, this research sought to identify the various kinds of regional development policies put into practice in Commonwealth African nations. This study looked for issues with regional development policy implementation in particular African countries as well as the effects of regional development policy indicators in those African countries. The main aim of thesis was to assess the level of implementation of regional policies in the Commonwealth countries in Africa. Data used for the analysis was from a field survey using a quantitative questionnaire data collection method. A 200-sample size was taken to treat this thesis and each of the four selected countries had a size of fifty respondents respectively. The study found that there were no regional development strategies in selected countries, and this came with inadequate funding hindered policy implementations that usually result to low level policy result and effects.
Keywords: regionální rozvoj; ekonomický rozvoj; politika regionálního rozvoje; implementace regionální politiky; Commonwealth Africa; economic development; regional development policy; policy implementation; Commonwealth Africa